The Effects and Adverse Reactions of Different Bowel Cleansers on Gut Microbiota After Colonoscopy - Hu, Jiabin; Peng, Xiongqun; Cai, Shuang; Qiu, Jiaojiao; Wang, Shuxia; Zhu, Ping (Turkish Journal of Gastroenterology, 2025)
Colonoscopy is a pivotal technique for screening and diagnosing colorectal diseases, particularly colorectal polyps and cancers. Early detection of lesions enables early diagnosis and treatment, thereby improving patient prognosis. The adequacy of bowel preparation is directly related to the quality and effectiveness of colonoscopy. However, the bowel cleansing process may disrupt the balance of gut microbiota, subsequently affecting the host’s health status. Currently, there is a relative scarcity of reports on the specific impacts of different types of laxatives on gut microbiota. Therefore, this paper aims to deeply analyze and summarize the effects of various bowel preparations on gut microbiota and their potential adverse reactions following colonoscopy, providing a more comprehensive reference for the selection of bowel preparations in clinical practice. Cite this article as: Hu J, Peng X, Cai S, Qiu J, Wang S, Zhu P. The effects and adverse reactions of different bowel cleansers on gut microbiota after colonoscopy. Turk J Gastroenterol. 2025;36(10):620-628.